Sequence stratigraphy, quaternary basin analyses in the Adriatic Foredeep - GURI, S.; GJANI, L.; RANXHA, S.; GURl, M.; XHAXHIU, A. (Bulletin of the Geological Society of Greece, 2018)
This paper intends to give the characterization of Quaternary loose deposits, near and along the sea coast zone, by evaluating lithological-geologic parameters, depositional environments and the tectonic subsidence. The main objectives are: - The lithologic-facial zone by mapping of lithologie composition and facies distribution. - The Quaternary basin analyses by interpreting depositional sequences of third order, where system tracts (lowstand, shelf wedge, transgressive and highstand) are individualized. - The present fluvial processes and delta configuration (Shkumbin, Seman).